The Effect of Profitability and Company Value on Stock Prices in Health Sector Companies Listed on The Indonesia Stock Exchange for The Period 2020-2024 - Wahyuni, Zalsabillah Cahya; Musa, Chalid Imran; Anwar; Nurman; Rahman, Abdul (Economics and Business Journal (ECBIS), 2026)
This study aims to examine the influence of profitability and firm value on stock prices in health sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. A quantitative approach with a documentation method was employed in this research. The population consisted of all health sector companies within the specified period, while the sample was selected using a purposive sampling technique based on predetermined criteria, resulting in a total of 15 companies. Data were analyzed using panel data regression through the Economic Views (EViews) 12 software. The findings of this study indicate that, profitability (ROA) has a positive and significant effect on stock prices of health sector companies for the 2020–2024 period. Similarly, firm value (Tobin’s Q) also shows a positive and significant influence on stock prices within the same period